Girls dancing to music outdoors - Unknown:::Creator::::::::::::
Photograph shows four young girls dancing by a large stone hearth while another girl stands on the attached stone bench and watches them. There is a phonograph playing a record on the bench beside her. They are at the YWCA's Camp Ayun Mapu in Big Basin, California.